Study on influence factors of public participation willingness in substation project based on integrated TPB-NAM model - Ma, Xin; Li, Junpeng; Guo, Fuli; Cui, Caocao; Chen, Tengfei; Xv, Fan; Wang, Wenbin (Frontiers in Psychology, 2022)
Public infrastructure, such as substations, is crucial for the advancement of the economy and society. However, the “not in my backyard” phenomenon is causing concern among the population, and these two things are at odds with one another. This study aims to investigate the driving mechanism that influences participation willingness of the public in order to promote the construction of substations, so the study proposes an integration model based on the planned behavior theory and the normative activation theory. Moreover, a structural equation model is created using the two dimensions, namely, social altruism and personal egoism, while data of 568 questionnaires are used for empirical research in combination with the “Decision-Making Trial and Evaluation Laboratory” method; these data are collected in the surrounding areas of three 110kV substations in Jiaozuo city, China. The key factors that affect participation willingness of the public are discussed, and the study demonstrates that the model is most significantly impacted by public trust, which is an a priori variable. Furthermore, the direct path coefficient of personal norms on participation willingness is the largest, which confirms that increased moral responsibility has a beneficial effect on project execution, and subjective norms contribute to the improvement of the assessment model overall since they are the main variables with the largest centrality degree in the system. The findings of this research better our understandings about the mechanism of “not in my backyard” and offer practical implications for its dissolution. On the basis of this, we present pertinent policy proposals for the “not in my backyard” effect that develops during the construction of public infrastructure.